Relative deprivation as a cause of risky behaviors - Oded Stark (University of Tübingen, Faculty of Economics and Social Sciences, 2019)
Combining a standard measure of concern about low relative wealth and a standard measure of relative risk aversion leads to a novel explanation of variation in risk-taking behavior identified and documented by social psychologists and economists. We obtain two results: (1) Holding individual i's wealth and his rank in the wealth distribution constant, the individual's relative risk aversion decreases when he becomes more relatively deprived as a result of an increase in the average wealth of the individuals who are wealthier than he is. (2) If relative deprivation enters the individual's utility function approximately linearly then, holding constant individual i's wealth and the average wealth of the individuals who are wealthier than he is, the individual's relative risk aversion decreases when he becomes more relatively deprived as a result of a decline in his rank. Our findings provide a theoretical support for evidence about the propensity of relatively deprived individuals to gamble and resort to other risky behaviors.
urn:nbn:de:bsz:21-dspace-945860
Keywords: D01; D81; D91; I12; 330; Social preferences; Relative deprivation; Concern about low relative wealth; Risk aversion